Localization and functional characterization of the p.Asn965Ser (N965S) ABCA4 variant in mice reveal pathogenic mechanisms underlying Stargardt macular degeneration. (14th November 2017) - Molday, Laurie L; Wahl, Daniel; Sarunic, Marinko V; Molday, Robert S
Abstract: ABCA4 is a member of the superfamily of ATP-binding cassette (ABC) proteins that transports N -retinylidene-phosphatidylethanolamine ( N -Ret-PE) across outer segment disc membranes thereby facilitating the removal of potentially toxic retinoid compounds from photoreceptor cells. Mutations in the gene encoding ABCA4 are responsible for Stargardt disease (STGD1), an autosomal recessive retinal degenerative disease that causes severe vision loss. To define the molecular basis for STGD1 associated with the p.Asn965Ser (N965S) mutation in the Walker A motif of nucleotide binding domain 1 (NBD1), we generated a p.Asn965Ser knockin mouse and compared the subcellular localization and molecular properties of the disease variant with wild-type (WT) ABCA4. Here, we show that the p.Asn965Ser ABCA4 variant expresses at half the level of WT ABCA4, partially mislocalizes to the endoplasmic reticulum (ER) of photoreceptors, is devoid of N -Ret-PE activated ATPase activity, and causes an increase in autofluorescence and the bisretinoid A2E associated with lipofuscin deposits in retinal pigment epithelial cells as found in Stargardt patients and Abca4 knockout mice. We also show for the first time that a significant fraction of WT ABCA4 is retained in the inner segment of photoreceptors. On the basis of these studies we conclude that loss in substrate-dependent ATPase activity and protein misfolding are mechanisms underlying STGD1 associated with the p.Asn965Ser mutation in ABCA4. Functional and molecular modeling studies further suggest that similar pathogenic mechanisms are responsible for Tangiers disease associated with the p.Asn935Ser (N935S) mutation in the NBD1 Walker A motif of ABCA1.